2021
DOI: 10.3389/fpsyg.2020.621248
|View full text |Cite
|
Sign up to set email alerts
|

e-Banking Adoption: An Opportunity for Customer Value Co-creation

Abstract: The development of information and communication technologies offers innovative opportunities to establish business strategies focused on customer value co-creation. This situation is especially notable in the banking industry. e-Banking activities can support competitive advantages. However, the adoption of e-banking is not yet well-established among consumers. In this sense, the technology acceptance model (TAM) is considered essential in studying consumer behavior applied to adopt a particular technology. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 49 publications
(108 reference statements)
2
32
0
1
Order By: Relevance
“…A series of previous studies indicated that perceived usefulness is positively associated with behavioral intention (Persico et al, 2014;Kumar Kakar, 2017;Chen and Wu, 2020). Perceived usefulness mediates the relationship between perceived ease of use and intention (Park et al, 2007;Carranza et al, 2021). Based on the empirical support from prior research, this present study seeks to revalidate similar relationships in the context of payment for livestream sports subscriptions.…”
Section: Hypotheses and Research Model Perceived Usefulnessmentioning
confidence: 90%
See 1 more Smart Citation
“…A series of previous studies indicated that perceived usefulness is positively associated with behavioral intention (Persico et al, 2014;Kumar Kakar, 2017;Chen and Wu, 2020). Perceived usefulness mediates the relationship between perceived ease of use and intention (Park et al, 2007;Carranza et al, 2021). Based on the empirical support from prior research, this present study seeks to revalidate similar relationships in the context of payment for livestream sports subscriptions.…”
Section: Hypotheses and Research Model Perceived Usefulnessmentioning
confidence: 90%
“…Different countries have different levels of development of the live football online platforms, while users in other countries have different payment behaviors. Future studies should expand the effective range of samples and the quantity with a wider geographical area (Tsai et al, 2020;Carranza et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The The findings of the study demonstrated that all the m-banking dimensions put a significant impact on customer value co-creation however, perceived usefulness puts the highest impact. It means that managers need to focus on usefulness because the customer will use the services if it will be useful to customers and hence will help in value creation of services of bank (Carranza et al, 2021;Galdolage, 2021;Ngo, Kohda, & Huynh, 2021). These findings are also reported in the study of Mostafa (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Co-creation by customers not only allows customer participation but also adds to the value of services of banks (Prahalad & Ramaswamy, 2004a, 2004b. Carranza, Díaz, Sánchez-Camacho, and Martín-Consuegra (2021) conducted a study on banking sector. The basis of this study lied in the theoretical foundations of TAM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Pakistan, the need for banking services is increasing day by day. Though in order to meet this need, the branches are being increased by the listed banks in Pakistan, still the accuracy and agility in the provision of banking services like fund deposits& transfers, withdrawals, management of current and savings accounts, loan management, applications for financial products and account services are needed (Carranza, Díaz, Sánchez-Camacho, & Martín-Consuegra, 2021;Li et al, 2021;Nawaz, Seshadri, et al, 2021). The accuracy, effectiveness, and agility of banking services can be improved with the use of innovative technology.…”
Section: Introductionmentioning
confidence: 99%